Neurotoxicity Assessment of Artemether in Juvenile Rats. (11th March 2013) - Beckman, David A.; Youreneff, Maureen; Butt, Mark T.
<x xml:space="preserve">Abstract</x> BACKGROUND Oral administration of artemether in combination with lumefantrine is approved for the treatment of malaria in adults and children. In adult animals, artemether can produce neurotoxicity with intramuscular, but not oral, administration. Herein, the potential of orally administered artemether to produce neurotoxicity in juvenile rats was investigated. METHODS In the first study, the toxicity of artemether was evaluated in juvenile rats dosed with 0, 10, 30, and 100mg/kg/day on postpartum days (ppds) 7 to 21. In‐life, clinical pathology, anatomic pathology, behavioral, and toxicokinetics evaluations were performed. The second study focused on neurotoxicity during different dosing intervals, with doses of 0, 30, and 80mg/kg/day on ppds 7 to 13, and doses of 0, 30, and 120mg/kg/day on ppds 14 to 21, 22 to 28, and 29 to 36. For each dosing interval, in‐life, extensive histology, toxicokinetics, and behavioral evaluations were performed. In the third study, toxicokinetics evaluations in the adult were conducted at 20 and 200mg/kg/day. RESULTS The first study demonstrated increased mortality, renal necrosis, and brain hemorrhage at ≥30mg/kg/day with no persistent effects in surviving animals. In the second study, increased mortality, body weight effects, and a trend toward increased exposure were observed in the ppd 14 and younger animals. Neither specific neurotoxicity nor persistent effects were seen. The toxicokinetic study in adults revealed lower exposures as compared to those in the younger juvenile rats. CONCLUSIONS As in the adult rat, oral administration of artemether in the juvenile rat is not associated with the neurotoxicity produced by intramuscular administration.